Global exponential stability of a class of neural networks with unbounded delays - Tran Thi Loan; Duong Anh Tuan (Український математичний журнал, 2008)
In this paper, the global exponential stability of a class of neural networks is investigated. The neural networks contain variable and unbounded delays. By constructing a suitable Lyapunov function and using the technique of matrix analysis, some new sufficient conditions on the global exponential stability are obtained.